A legitimação da ginástica de academia na modernidade: um estudo da década de 1980 - Toledo, Eliana de (2010)
This research was planned after an analysis of the fact that even now physical exercise in fitness centers seems to be of utmost importance to get an active and socially succeeded body. The main objective of the study was to understand why physical exercises reach so high legitimacy in our days, especially in Brazil, not only in body building according to media patterns, but also as if it were a natural must have , a passport to reach health and also some beauty patterns. The eighties were selected as an historical approach as they were marked by the boom of physical exercise in fitness centers in the country. Two methodologies were used in order to reach the objective of the study: the oral history, using oral testimonies with physical educators; and the other was the documental analysis of Veja magazine copies, choosen by it´s wide range of subjects reaching many sectors of public life. Many factors contributed to the legitimacy of physical exercises in fitness centers in that time, as: a transition of government models (dictatorship/democracy); the American influence; the acceleration of midia segmentation followed by the increase of the body visibility; the advance of the technology that, among other aspects, propelled medical researches; the influence of the Cooper Method and of all the activity generated and/or fortified by it for the benefit of a health body (being the aerobics gymnastics a part of it); the second feminist revolution, etc. It was possible also to conclude that many of these factors both influentiated and legitimated each other. Being so, this research collaborates to broaden the studies in this area, in the direction of new views, as well as to identify the feasibility of ruptures and permanences since the eighties till now